Analysis of a High-Rise Structure Considering Shear Walls of Different Materials with different Positioning using ETABS : A Review - Roshni Kandulna; Dharmendra Prajapati; Anudeep Nema (International Journal of Scientific Research in Civil Engineering, 2022)
Shear walls are the structural systems which counteracts the effect of lateral loads such as wind and earthquake loads acting on a structure. They are usually provided as an encasement for the elevator cores, stairwells etc., thereby resisting the horizontal and vertical forces effectively. In the present study, analysis of RCC building has been carried out by changing the locations of shear walls in the building. Also, the effect of variations in seismic zones as per IS codes has been presented. The seismic analysis performed is linear dynamic response spectrum analysis using the well known analysis and design software ETABS16.2.0. Seismic performance of the building has been investigated based on parameters such as storey drift, base shear and storey displacements. In this paper we are presenting review of litertaures related to